Oxford Business English Dictionary for Learners of English - Parkinson, Dilys (Oxford Oxford University Press, 2005)
This new, up-to-date dictinary gives you all the help and information you need to do business in English. It explains more than 30,000 words, phrases and meanings in language you can understand, with examples so you use the words correctly. It shows you the 1,000 most important words you need to learn. Intermediate to Advanced Level.
Keywords: Business English